The Contribution of Metaphor to Islamic Education Learning - Nazar, M. (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2022)
This study was conducted as an attempt to show that the Qur'an was revealed by using a high, charming, and touching language style through one of the grammatical elements, namely the metaphorical style. This study uses library research. The analysis is carried out by referring to the sciences of Indonesian grammar, Arabic, and Arabic-English Dictionary Quranic Usage: Handbook of Oriental Studies by Elsaid M. Badawi and Muhammad Abdel Haleem. Then some verses of the Qur'an are taken as examples of metaphors. This study found that the Qur'an as a competency learned in Islamic religious education (Pendidikan Agama Islam/PAI) learning has many metaphorical elements that are less aware of its existence. The metaphorical style of language becomes one of the tools to translate the Qur'an properly and correctly.